Avaliação do uso de lodos de estação de tratamento de água como matéria-prima na confecção de tijolos cerâmicos: estudo de caso - ETA Bolonha - MULLER, Elzelis de Aguiar (Universidade Federal do Pará, 2012)
This study aimed to evaluate the possibility of incorporating the sludge in the water treatment station of Bolonha (RMB), in the manufacture of ceramic bricks for use in construction. Two units of flow of mud (UDL) were established and operationalized in the ETA Bolonha. Before the preparation of ceramic bricks, the mud flows were ETA Bologna in UDL's that were equipped with open collar, and then were characterized physically and mineralogically. The sludge was added to the ceramic body of a local industry for the production of bricks. Various proportions of silt and clay mixture were tested in order to find the appropriate proportion to the production of ceramic bricks (10%, 12% and 20% of sludge in the ceramic body ETA). Laboratory tests were conducted to assess its strength, water absorption, an appropriate size and visual appearance. It was not possible to incorporation of 20% of mud to ceramic body due to the high plasticity and the difficulty of manufacture of ceramic bricks, however, the proportions of 10% and 12% of sludge from ETA were the ones that had better results on the parameters of resistance, indicating that the ceramic bricks can be produced with the incorporation of up to 12% of sludge from ETA.